Influential factors on political participation of public university undergraduates in Hebei Province, China. - Yang, Yanan; Xia, Nan; Ahmad, Zaid; Jawan, Jayum; Talib, Ahmad Tarmizi (Canadian Center of Science and Education, 2018)
In recent decades, political participation amongst young people has attracted much academic research in established democracies. However, as an understudied area in China especially in Hebei province, political participation of public university undergraduates is in low level. Thus, this article concerns the political participation of public university undergraduates in Hebei province of China. The objective of this article is to identify the influential factors and determine the principal influential factor to students’ political participation in the public university of Hebei province. Therefore, 1990 respondents were selected based on the cluster sampling method, the main statistical method for evaluation of research hypotheses is by the PLS-SEM. Findings of this study indicate that political education has neither effect nor relation to political participation, whereas university identity, experience, major integrated undertake directly function on political participation. Moreover, political competence is the most important for students’ political participation in the public universities of Hebei province, China. Political value cognitive ability is the most important competence which influences the level of political participation among all involved factors in influencing students’ political participation in Hebei public universities according to the results of Importance-Performance Map Analysis (IPMA) and Structural Equation Modeling (SEM). Additionally, the author suggested that in order to improve students’ participatory level, enhancing capability of students is a necessary way.